Development of Game Recognition Covid-19 Variants, Symptoms, and Vaccinations Based on RPG - Saputri, Fiqih Hana; Ferawati, Ferawati (Politeknik Ganesha Medan, 2022)
Technology is required to support the learning process in education, especially amid the present Covid-19 pandemic, which necessitates pupils to study from home. Obviously, online learning between students and teachers requires liaison media as a means of communication to facilitate the learning process, one of which is the introduction of variation, symptoms, and Covid-19 immunization, which many youngsters do not yet comprehend. Therefore, games are required to introduce variations, symptoms, and Covid-19 vaccinations in order to provide students with the necessary information to recognize variations, symptoms, and Covid-19 vaccinations. A game created with RPG Maker MV that features characters. There are six grade levels in the game. To proceed to the next grade level, kids must answer questions within each game. Based on the questionnaire responses using the SQA measure, this game received a score of 83.6 out of a possible 100. Similarly, the feasibility of quality has a value of 82.2. The questionnaire scores varied by 2.4 points, and it was determined that the variance, symptom, and Covid-19 vaccine recognition game was usable. This game can be used as a resource for introducing and preventing Covid-19 among students.